Bukit Chapalang: the mousedeer in the formation of a nation - Kheong, Christopher Quah Wai; Anita Harris Satkunananthan, (Penerbit Universiti Kebangsaan Malaysia, 2023)
This paper is a neo-archetypal interrogation of Sang Kancil in his role as the archetypal Politician. This is based on an analysis of the works of Sonny Liew (2015) a Malaysian born artist, The Art of Charlie Chan Hock Chye (2015), which utilises the iconography of the mousedeer in the formation of a nation. In the book, there is a short section called Bukit Chapalang, which is Liew ‘s (2015) revisioning of Sang Kancil as the Singaporean premier Singaporean Chinese Premier Lee Kuan Yew. This is done by comparing the original folktales of Sang Kancil with that of present-day retellings, done by Liew (2015). The changes that have occurred to Sang Kancil will be analysed using the two types of archetypal theories which are Jungian-archetypes and Neo-archetypes. From the study we expect to find the ways in which animals can be used as archetypal allegories to describe a story, such as a historical event, and can identify the changes that occur to the trickster figure of Sang Kancil when transposed to a Singaporean political landscape.